Minerals Beneficiation - The Role of Inorganic Ions in the Flotation of Beryl - K. V. Viswanathan; V. M. Karve; J. Y. Somnay; K. K. Majundar (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1965)
The effect of calcium, magnesium, iron (both ferrous and ferric) and aluminum ions, which are commonly encountered in a typical beryl ore, was studied in the flotation of pure beryl, soda-feldspar and quartz. The vacuumatic flotation technique was employed. With sodium oleate as collector and in the absence of any activator, beryl floated in a pH range of 3 to 7.5, whereas feldspar and quartz did not float at any pH up to 11.5. The pH range of flotation increased in the presence of the ions studied. With calcium and magnesium ions beryl floated from 3 to 11.5 pH and beyond, soda-feldspar floated beyond pH 6 and quartz floated beyond pH 8. Ferrous ion activation was found to be similar to that of calcium and magnesium. Activation by ferric and aluminium ions was found to be complex and the lower and upper critical pH for all the three minerals was around 2 and 10 respectively. These studies indicated the possibility of separation of beryl from feldspar and quartz even in the presence of calcium, magnesium and ferrous ions between pH 4 and 6. Flotation tests on a mixed feed of pure minerals in a 10 g cell revealed that beryl can be selectively floated from feldspar and quartz if ferric ion is reduced to ferrous state or if it is complexed. Beryl occurs mostly in pegmatites, and hence is associated with feldspar, quartz and micas and small amounts of other minerals such as apatite and tourmaline. The separation of beryl from these minerals is difficult because all the silicates accompanying beryl have more or less the same physical properties. Specific gravities of beryl, feldspar and quartz are 2.70, 2.56 and 2.66 respectively. Electrostatic separation has been suggested but no work has been reported. ' The adsorption of sodium tri-decylate tagged with Cl4 on beryl, feldspar and quartz reveal similarity in surface properties. Much work has been reported on the flotation of beryl from ores, either directly or indirectly as a by-product, but little is known about the fundamental aspects of beryl flotation. Kennedy and O'Meara3 laid emphasis on prior cleaning of the mineral surfaces with HF. Mica is removed first by flotation of beryl with oleic acid, around neutral pH. Runke4 introduced calcium hypochlorite conditioning in a final separation stage for activating beryl in a mixed beryl-feldspar concentrate, and after washing to remove the hypochlorite, floated beryl with petroleum sulphonate. The Snedden and Gibbs5 procedure is somewhat similar to that of Kennedy and O'Meara. Emulsified oleic acid is used as collector. Recently Fuerstenau and Bhappu6 studied the flotation of beryl, feldspar and quartz with petroleum sulfonate in the presence of activators and stressed the importance of iron in the flotation of beryl. From the studies conducted in this laboratory, it was found that feldspar and quartz as such do not float with sodium oleate, but in practice selective flotation of beryl from feldspar and quartz in an ore is found to be impossible with sodium oleate as collector. A glance at the chemical analysis of typical beryl ore indicates the presence of several ions like Ca ++, Mg++, Al + + + and Fe+++ in abundance and Ti++++ and Mn++ in traces. Hence, in an attempt to explain the behaviour of feldspar in the beryl flotation, the effect of Ca++, Mg++, Al+++ and Fe+++, which are known as gangue mineral activators7'8 has been investigated. Materials and Methods: Lumps of beryl ore (hand picked) were boiled with 10% sodium hydroxide and washed with distilled water. They were further boiled many times with 10% hydrochloric acid till no positive test for iron was obtained with ammonium thio cyanate. This was followed by thorough flushing with double distilled water. The lumps were crushed in a porcelain mortar and pestle under water. The minus 65 + 100 mesh fraction was used for testing and was always stored under distilled water. Pure feldspar and quartz were similarly prepared and the minus 65 + 100 mesh fractions collected. Inorganic ions tried as activators were ca++, Mg++ , Fe++, Fe ++ and A1 +++ . Calcium nitrate, magnesium chloride, ferrous ammonium sulfate, ferric ammonium sulfate and aluminum nitrate of G.R.E. Merck grade were used. B.D.H. technical grade sodium oleate was used as a collector. The vacuumatic flotation technique developed by Schuhmann and Prakash was used for studying the effect of pH on flotability. 7 The indications given by this work were confirmed by using 10 g miniature cell.'